KAJIAN PERBANDINGAN OPTIMALISASI PENJADWALAN DAN BIAYA PROYEK DENGAN METODE LEAST COST SCHEDULING - Yusrizal Lubis; Diana Suita (Universitas Harapan Medan, 2020)
In making a comparison of the unit price of work (HSP) using the 2016 SNI regulations in the implementation of the construction of the AJIBATA Public Health Center, which is located on Jln. Construction of 2 AJIBATA, Pardemean AJIBATA, District, AJIBATA, Toba Regency, North Sumatra Province. The comparison is carried out using the 2016 Work Unit Price Analysis (AHSP) and the 2021 Work Unit Price Analysis (AHSP) by comparing the two analyzes used to see the comparison of material prices, wages, in each year and also the results of the second comparison. This analysis can be used as a reference in the future in carrying out the construction of other public facilities. In this stage, the data obtained directly in the field are used and also the plan drawing data used in calculating all the volumes of work to be carried out. The price of materials and wages in each region is very influential in the implementation of project development, so research is carried out to get a better price so that the use of funds can be maximized as well as possible. In the comparison of Work Unit Price Analysis (AHSP) 2016 and Work Unit Price Analysis (AHSP) 2021, the cost comparison of all work items between the two analyzes is 15%, of which the 2016 Unit Price Analysis (AHSP) has a cost of IDR 3,758. 157,389,76 and Analysis of Work Unit Price (AHSP) 2021 Rp. 4,337,533,610,2, . From the results of the second comparison, the analysis used does not include overhead / profit.